Efectividad del programa Educativo:"Lonchera Sanita" en el Nivel de Conocimiento Sobre Loncheras en Madres y/o Cuidadores de Preescolares con Problemas Nutricionales de las I.E.I de Quirihuac, Bello Horizonte y Santa Rosa del Valle Santa Catalina-2008 - Castro Velásquez, Claudia Lisset (2008)
This investigation study, of pre-experiment type, was realized in Qirihuac, Bello Horizonte and Santa Rosa’s kindergardens at Valle Santa Catalina, during June - October of 2008, with the purpose of determining the educational program's effectiveness “Lonchera Sanita” in the knowledge level on lunch boxes in mothers and/or people who take care of preschool students with nutrition problems. The sample was constituted of 27 mothers and/or people who take care of preschool students who obeyed the inclusion criteria mentioned in the investigation. To obtain the data we used the instrument: Rank of Knowledge on Lunch Boxes (RKLB), being the obtained information processed and analyzed by: The statistical test for correlated data “t de student”, the results are presented in simple tables, double entrance tables and graphics. The following conclusions were reached after the analysis: - Before the application of the educational program, the 48,15 percent of mothers and/or people in charge of preschool students got a medium knowledge level. - After the educational program's application, the majority of mothers and/or people in charge of preschool students got a high- knowledge level 77,80 percent. - The educational program was effective to the improving the knowledge level of mothers and/or people who are in charge of preschool students with nutrition problems. Key words: Educational program, knowledge about lunch boxes, mothers and/or people who take care of preschool students.